Determining the best timing of insemination based on salivary fern pattern and its association with conception in buffalo - Pokharel, A.; Gautam, G.; Shah, S.; Yadav, K.D.; Rekik, Mourad; Deka, Ram Pratim; Varijakshapanicker, Padmakumar; Devkota, B. (Elsevier, 2025)
Salivary fern patterns (SFP) offer a simple, non-invasive, and cost-effective alternative to conventional estrus detection methods, addressing challenges such as silent heat, inaccurate heat detection, and improper timing of artificial insemination (AI). This study evaluated the utility of SFP in determining best timing for AI and its association with conception in buffaloes. Two experiments were conducted. In Experiment 1, twelve cyclic buffaloes in follicular phase were treated with standard Ovsynch protocol and 168 saliva samples were systematically collected to establish reference SFP, its grades, and corresponding fractal dimension values across the luteal and follicular phases. In Experiment 2, 62 buffaloes in natural estrus were inseminated without hormonal treatment, with saliva samples collected prior to insemination for SFP analysis. The SFP were graded as excellent, good, fair, or poor based on microscopic observation and fractal dimension values. During Experiment 1, an excellent grade SFP with lower (P<0.01) fractal dimension values was observed during late proestrus and early estrus. In about 15 hours, the grading transitioned to a good grade corresponding to late estrus before declining to fair or poor grades in the luteal phase. In Experiment 2, buffaloes exhibiting a good grade SFP at insemination showed higher conception rates (P<0.01) compared to other grades. These findings suggested a precision AI timing for improved conception in buffaloes at either 15 hours after the appearance of an excellent grade SFP or when the SFP grade transitions to good, corresponding to late estrus. This approach may help enhance reproductive efficiency and address estrus detection challenges in buffaloes.